Application of Subjective and Objective Empowerment in Evaluation of ideological and political Distance Learning Online Teaching - Cui, Yu; Wang, Lijuan; Li, Lemin (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Distance network teaching has been widely used in today’s informationization era, and it also provides a new teaching mode for ideological and political education. However, evaluating the quality of ideological and political distance network teaching still needs to be solved. OBJECTIVES: To solve the problem of subjective solid dependence in its evaluation, the hierarchical analysis method and entropy weighting method are used to calculate the subjective and objective weights, and the principle of minimum information identification is used to determine the optimal comprehensive consequences of the indicators, taking into account the absolute subjectivity and absolute objectivity brought about by the calculation method of the weights of the hands. METHODS: Considering the incompatibility of grade determination in the evaluation results, the evaluation grade determination of Civics remote network teaching is completed through the table evaluation model, and the table evaluation model of Civics remote network teaching based on the principle of minimum information discrimination with combined weights is finally established, and the application of the model is carried out. RESULTS: The evaluation model is simple and practical and improves the efficiency and operability of comprehensive evaluation. CONCLUSION: Civics remote network teaching will further broaden the sharing and dissemination channels of educational resources and needs to improve the quality and effect of education continuously, and the study has a good application prospect for the evaluation of Civics remote network teaching.